2016
DOI: 10.1039/c6tb01480a
|View full text |Cite
|
Sign up to set email alerts
|

Differential internalization of brick shaped iron oxide nanoparticles by endothelial cells

Abstract: Nonspherical iron oxide core “nanobricks” have enhanced uptake in endothelial cells through caveolae-mediated endocytosis mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…These earlier results on polystyrene nanoshapes are in stark contrast to our own data on IO nanospheres and nanobricks [ 42 ]. We examined the influence of IO NP shape in regulating preferential uptake specifically in endothelial cells (brain, lung).…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These earlier results on polystyrene nanoshapes are in stark contrast to our own data on IO nanospheres and nanobricks [ 42 ]. We examined the influence of IO NP shape in regulating preferential uptake specifically in endothelial cells (brain, lung).…”
Section: Introductioncontrasting
confidence: 99%
“…While there are numerous papers that describe methods for creating non-spherical IO nanostructures [ 30 ] (particularly wires [ 23 , 31 ], rods [ 32 , 33 , 34 , 35 , 36 ], cubes [ 37 , 38 , 39 ], and sheets [ 40 ]), fewer of those are used or investigated for in-depth (bio)medical research. While there is a wealth of data for T2 MRI contrast enhancement and magnetic hyperthermia use of such IO nanoshapes [ 41 ], specific cell uptake [ 42 ] in various relevant tissue or cancer cell lines as well as their intracellular behavior have remained, to a large extent, unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, BSA binding to CNPs promoted their uptake through SR-As due to albumin denaturation upon adsorption [ 173 ]. However, other studies have reported that serum protein adsorption, both in vitro and in vivo, may decrease ION uptake due to attenuation of surface charge and increased nanoparticle agglomeration [ 153 , 174 ]. These adsorbed proteins have also shown to be major contributors to their in vivo recognition by macrophages and the reticuloendothelial system through opsonin receptors.…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
“…Sun et al investigated the impact of iron oxide nanobricks on mouse‐brain derived microvessel endothelial cells (bEnd.3) in comparison to identically functionalized nanospheres . Both nanobricks and spheres were silanized to attach carboxy groups onto their surfaces, resulting in negatively charged materials (ζ‐potential −39 mV for spheres, −45 mV for bricks).…”
Section: Particle Properties and Resulting Implications On Particle–cmentioning
confidence: 99%